A responsive magnetic Cr(Ⅵ) sensor and a preparation method and application thereof
Patent Information
- Application Number
- CN202311012354.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-08-11
AI Technical Summary
[0002]六价铬(Cr6+)具有强烈的毒性,可能造成遗传性基因缺陷,对人类及环境具有持久性危害
[0023](1)本发明的“开封”型传感器有效针对酸性水体中的Cr6+,利用Fe3O4/RhB@PAM在酸性环境中因PAM水解氧化及Cr6+还原沉淀引起的前后荧光信号的变化来实现Cr6+的高效检测。
Smart Images

Figure CN117129452B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a responsive magnetic Cr(VI) sensor, its preparation method and application, belonging to the field of new material preparation and water metal ion sensing and detection technology. Background Technology
[0002] Hexavalent chromium (Cr) 6+ Cr is highly toxic, may cause hereditary genetic defects, and poses a persistent threat to humans and the environment. The International Agency for Research on Cancer (IARC) of the World Health Organization has classified Cr as a Class II protected animal. 6+ It is classified as a Group 1 carcinogen. Traditional Cr... 6+ The detection methods suffer from problems such as complex operation, long time consumption, low sensitivity, poor selectivity, and some instruments are cumbersome to operate and have high analysis costs.
[0003] Fluorescence spectroscopy has become a leading method in many analytical applications due to its high sensitivity, high selectivity, and ease of operation. Nanosensors constructed by combining fluorescent molecules with hydrophilic materials have been applied in the field of metal ion detection (CN 108559485 A, CN 112708015 B). Research results show that the hydrophilicity of fluorescent molecules is improved after loading, and some can even achieve adsorption and scavenging while detecting metal ions. However, these reported nanosensors rarely involve Cr. 6+ The sensing of ions is complicated, costly, and its application is limited to neutral or slightly alkaline water environments (CN106248641A, CN 106370612 B, CN 108445053 A).
[0004] Therefore, existing methods for detecting Cr 6+ The molecular sensor cannot be separated when used in a homogeneous system. Furthermore, existing improved Cr... 6+ Most nanosensors are expensive to manufacture and rarely involve acidic, Cr-containing environments. 6+ Its application in wastewater, and the fact that it is not easy to separate quickly, can easily cause secondary pollution. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a responsive magnetic Cr(VI) sensor, its preparation method, and its application. The sensor of this invention belongs to the category of "open-type" acid-responsive sensors, capable of rapidly detecting Cr in acidic wastewater. 6+ The detection is highly sensitive and selective. Furthermore, the sensor, after detection, can rapidly accumulate the substance under the influence of an external magnetic field using its own magnetism, thus separating it from the water and avoiding secondary pollution.
[0006] This invention is achieved through the following technical solution:
[0007] This invention first provides a responsive magnetic Cr(VI) sensor, which is a nanosensor Fe3O4 / RhB@PAM formed by embedding Fe3O4-NH2 nanoparticles with Rhodamine B through the polymerization of acrylamide.
[0008] Preferably, the mass percentages of Fe3O4-NH2 nanoparticles, Rhodamine B, and polyacrylamide (PAM) in the Fe3O4 / RhB@PAM nanosensor are 8.7%–17.7%, 3.5%–17.8%, and 73.4%–86.3%, respectively.
[0009] This invention also provides a method for fabricating a responsive magnetic Cr(VI) sensor, comprising the following steps:
[0010] (1) Carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were dispersed in phosphate buffer (PBS), polyethylene glycol dicarboxylic acid was added, and the mixture was stirred and activated at room temperature for 4-6 h. Then, PBS buffer solution of Fe3O4-NH2 particles was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated, washed, and then dispersed again in PBS buffer. EDC and NHS were added and activated for 4-6 h. Then, 1,6-hexanediamine PBS buffer was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated and washed to obtain amidated Fe3O4-NH2 nanoparticles.
[0011] (2) The amidated Fe3O4-NH2 nanoparticles obtained in step (1) were dispersed in deionized water, and Rhodamine B aqueous solution was added. The mixture was stirred thoroughly at room temperature for 100 min. Acrylamide, sodium hexametaphosphate, and potassium persulfate were then added. The mixture was stirred violently with ultrasound at 35-75℃ for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing with ethanol and deionized water, and vacuum drying.
[0012] Preferably, in step (1), the concentrations of carbodiimide (EDC) and N-hydroxysuccinimide (NHS) dispersed in phosphate buffer (PBS) are both 10 mg / mL.
[0013] Preferably, the weight ratio of carbodiimide (EDC), N-hydroxysuccinimide (NHS), polyethylene glycol dicarboxylic acid and Fe3O4-NH2 particles is 0.1:0.1:(1.55-2.35):(0.99-1.51).
[0014] Preferably, the weight ratio of 1,6-hexanediamine to Fe3O4-NH2 particles in the added 1,6-hexanediamine PBS buffer is 1:(1.98-3.02).
[0015] Preferably, in step (2), the weight ratio of amidated Fe3O4-NH2 nanoparticles, Rhodamine B in Rhodamine B aqueous solution, acrylamide, sodium hexametaphosphate, and potassium persulfate is (0.21-0.83):(0.07-0.43):(1.77-3.49):(2.44-11.02):(1.37-9.96).
[0016] More preferably, the concentration of the Rhodamine B aqueous solution is 0.01–0.18 mol / L.
[0017] Preferably, the Fe3O4-NH2 nanoparticles in step (1) are prepared by a solvothermal method. 1,6-hexanediamine is weighed and dissolved in ethylene glycol at a weight-to-volume ratio (g / mL) of 1:6. The solution is stirred in a 50°C water bath until completely dissolved. Then, FeCl3·6H2O and anhydrous sodium acetate are dissolved by ultrasonication. The solution is then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190°C for 6 hours. After cooling to room temperature, the solution is magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35°C to obtain Fe3O4-NH2 nanoparticles. The weight ratio of FeCl3·6H2O, anhydrous sodium acetate and 1,6-hexanediamine is 1:2:5.
[0018] This invention also provides the above-mentioned responsive magnetic Cr(VI) sensor in acidic Cr-containing environments. 6+ Applications in wastewater testing.
[0019] Preferably, the amount of the sensor used is 0.05 mg / mL.
[0020] The detection process is as follows: a responsive magnetic Cr(VI) sensor is added to an acidic environment containing Cr. 6+ The wastewater was shaken and the Cr in the reaction wastewater was monitored by fluorescence. 6+ The presence or absence of ions and the amount present.
[0021] This invention utilizes fluorescence spectroscopy to fabricate an acid-responsive Cr(VI) magnetic fluorescent sensor with good hydrophilicity, resembling a spherical morphology similar to a transparent capsule. The abundant amino groups in the polyacrylamide structural units endow the sensor with excellent hydrophilicity, particularly in acidic Cr(VI) environments. 6+ In water, the hydrolysis and oxidation of PAM and Cr in the Fe3O4 / RhB@PAM sensor were monitored. 6+ The fluorescence signal is altered by the reduction and precipitation of Cr, which acts as a "gate" to control the encapsulation of Rhodamine B. It exerts its sensing effect under acidic conditions, enabling rapid detection of Cr within a short time. 6+ Rapid and accurate detection.
[0022] The beneficial effects of this invention are:
[0023] (1) The "open-seal" type sensor of the present invention is effective against Cr in acidic water. 6+ The Fe3O4 / RhB@PAM reaction in an acidic environment utilizes the hydrolysis and oxidation of PAM and Cr... 6+ The change in fluorescence signal before and after reduction precipitation is used to realize Cr 6+ Highly efficient detection.
[0024] (2) The raw materials for preparation of this invention are widely available, low in cost, simple in preparation process, environmentally friendly and economical. The introduced Fe3O4 nanoparticles endow the sensor with magnetic response performance, so that the sensor after detection can be recycled by using its own magnetism to enrich the water body through an external magnetic field, thus avoiding secondary pollution to the water body.
[0025] (3) The Fe3O4 / RhB@PAM sensor of the present invention has high detection sensitivity and strong specificity, integrating fluorescence, magnetism and nanostructure physical properties, which can fully optimize molecular sensors and effectively overcome the limitations of existing Cr sensors. 6+ The limitations of detection technology, in Cr-containing 6+ It has great application potential in the field of wastewater detection and treatment. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 The XRD pattern of the Fe3O4 / RhB@PAM sensor prepared in Example 2;
[0028] Figure 2 The FT-IR image of the Fe3O4 / RhB@PAM sensor prepared in Example 2;
[0029] Figure 3 The stability of the Fe3O4 / RhB@PAM sensor prepared in Example 2 under different pH conditions and when detecting Cr(VI);
[0030] Figure 4 The graph shows the specificity results of the Fe3O4 / RhB@PAM sensor prepared in Example 2.
[0031] Figure 5 The image shows the sensitivity results of the Fe3O4 / RhB@PAM sensor prepared in Example 2. Detailed Implementation
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0033] Example 1
[0034] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0035] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer containing 0.256 g / mL Fe3O4-NH2 particles was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then re-dispersed in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added, and the mixture was activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0036] 0.83 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.16 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 3.49 g of acrylamide, 11.02 g of sodium hexametaphosphate, and 9.96 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 75 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0037] Example 2
[0038] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0039] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0040] 0.83 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.16 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 3.49 g of acrylamide, 11.02 g of sodium hexametaphosphate, and 9.96 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 35 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0041] Example 3
[0042] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0043] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0044] 0.21 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.04 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 1.77 g of acrylamide, 2.44 g of sodium hexametaphosphate, and 1.37 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 35 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0045] Example 4
[0046] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0047] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0048] 0.21 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.04 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 1.77 g of acrylamide, 4.17 g of sodium hexametaphosphate, and 3.75 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 35 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0049] Example 5
[0050] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0051] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0052] 0.21 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.18 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 1.77 g of acrylamide, 4.17 g of sodium hexametaphosphate, and 3.75 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 35 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0053] Example 6
[0054] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0055] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0056] 0.21 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.03 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 1.77 g of acrylamide, 4.17 g of sodium hexametaphosphate, and 3.75 g of potassium persulfate were added, and the mixture was stirred vigorously with ultrasound at 50 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0057] Test Example 1
[0058] The Fe3O4@RhB@PAM sensor prepared in Example 2 above was subjected to crystal form analysis using X-ray powder diffraction (XRD). The wavelength was... The scanning range is 10–80°. For example... Figure 1 As shown, by comparing with the standard card (JCPDS no. 46-0193), it was found that the diffraction peaks at 2θ at 30.23°, 35.37°, 43.29°, 56.72°, and 63.14° are consistent with the (220), (311), (400), (511), and (440) crystal planes of Fe3O4. This indicates that the polymerization and embedding process does not affect the crystal form of Fe3O4, and the sensor obtained has good magnetic properties.
[0059] Test Example 2
[0060] The Fe3O4 / RhB@PAM sensor prepared in Example 2 was subjected to surface structure analysis using an IR200 Fourier transform infrared spectrometer (FT-IR). The sample to be tested was ground into powder, and an appropriate amount of the sample was prepared using the KBr pellet method. The scanning range was 4000 cm⁻¹. -1 ~500cm -1 .like Figure 2 As shown, 580cm -1 The absorption peak at 3435 cm⁻¹ is caused by the Fe-O stretching vibration of Fe₃O₄; -1 The broad absorption peak at 1655 cm⁻¹ is caused by the characteristic stretching vibration of -OH. -1 The absorption peak at 1420 cm⁻¹ is the NH bending vibration peak of the amide in PAM; -1 The absorption peak at 1600–1400 cm⁻¹ is the CN stretching peak of the amide in PAM. -1 The absorption peaks within the range are skeletal vibration absorption peaks of the benzene ring, indicating that the polymerization of PAM effectively encapsulates RhB and Fe3O4, successfully preparing a magnetic sensor.
[0061] Test Example 3
[0062] The Fe3O4 / RhB@PAM sensor prepared in Example 2 above was used to perform a hexavalent chromium ion sensing and detection experiment, including the following steps:
[0063] A certain amount of Fe3O4 / RhB@PAM sensor was weighed and ultrasonically dispersed in a certain volume of ultrapure water to prepare a sensor stock solution (concentration of 50 ppm). Appropriate amounts of PbCl2, FeCl3, CdCl2, NaCl, KCl, CaCl2, SnCl2, and CrCl2 were weighed and dissolved in ultrapure water to prepare competing ion stock solutions with a concentration of 15 ppm each. The prepared 30 ppm Cr(VI) stock solution was diluted to prepare a 15 ppm Cr(VI) stock solution. First, the effect of Fe3O4 / RhB@PAM on Cr under different pH environments (pH 1-8) was studied. 6+ The stability and sensing capability of the sensor were assessed. Then, according to the experimental design, the sensor stock solution was mixed with the competing ion stock solution at the specified concentration and ratio. After ultrasonic vibration for 30 seconds and standing for 5 minutes, fluorescence spectroscopy was performed. Under the same conditions, Cr... 6+ Competition experiments with other ions were conducted. The resulting spectra were analyzed and studied to evaluate the sensor's response to Cr. 6 + The selectivity. Next, Cr 6+ After diluting the mother liquor proportionally (1–10 ppm), transfer the same volume of sensor stock solution and add it to the same volume of Cr solutions of different concentrations. 6+ In the solution, after ultrasonic vibration for 30 seconds and standing for 5 minutes, the fluorescence intensity was measured to analyze the sensor's response to Cr. 6+ Response sensitivity.
[0064] like Figure 3As shown, acidic environment studies indicate that the RhB intensity quenched by the Fe3O4 / RhB@PAM nanosensor increases at pH < 7, demonstrating its suitability for detecting Cr under acidic conditions. 6+ Ions; PAM hydrolyzes under slightly acidic conditions, and the hydrolysis rate increases with increasing temperature and decreasing pH. Figure 3 As shown in Figure F0, PAM hydrolysis accelerates as pH decreases from 6 to 3, and RhB in the Fe3O4 / RhB@PAM magnetic composite particles is released during PAM hydrolysis, resulting in enhanced fluorescence intensity. When Cr... 6+ In its presence, under acidic conditions at pH 3–7, PAM is oxidized, simultaneously producing Cr. 6+ It is reduced and precipitated as Cr(OH)3 (Cr2O7) 2- +14H + +6e - =2Cr 3+ +7H2O), which then "traps" and coats RhB, causing fluorescence quenching. When the acidity increases further, some of the Cr(OH)3 precipitate begins to dissolve, increasing the fluorescence intensity, such as... Figure 3 As shown in F, the increase in RhB intensity quenched at pH 3.0 is the largest. Therefore, the magnetic sensor's response to Cr was studied at pH 3.0. 6+ Detection of ions. Secondly, the detection performance indicates that the sensor is only effective against Cr. 6+ It exhibits low fluorescence intensity; under the same conditions, most metal ions would quench the fluorescence of this sensor to some extent. Furthermore, under the same conditions, Cr... 6+ When added to a solution containing competing ions, the corresponding fluorescence intensity decreased significantly (see attached diagram). Figure 4 This determined the effect of Fe3O4 / RhB@PAM magnetic composite particles on Cr 6+ It exhibits good specificity. When the sensor encounters Cr... 6+ At that time, under specific conditions, the sensor utilizes the hydrolysis and oxidation of PAM and its Cr 6+ The mechanism of reduction precipitation is used to control the "opening and closing" of RhB inside the sensor. "Opening" means that RhB is released to enhance fluorescence intensity, while "closing" means that RhB is sealed inside the sensor or coated to block fluorescence and quench it. This indicates that the Fe3O4 / RhB@PAM sensor designed and prepared in this invention has high sensitivity and specificity.
[0065] Furthermore, as we expected, with Cr 6+ As the concentration increases, the fluorescence intensity at 554 nm gradually decreases, exhibiting a linear relationship. (Appendix) Figure 5 When Cr 6+When the concentration increases to 5 mg / L, the fluorescence quenching effect suddenly changes dramatically, indicating that the sensor is sensitive to 5 mg / L Cr. 6+ The response is the most sensitive. This demonstrates that the functionalized magnetic fluorescent composite nanoparticles are a rapid detection method for Cr. 6+ The sensor, in acidic Cr 6+ It has shown great application potential in the field of wastewater detection and treatment.
[0066] The Fe3O4 / RhB@PAM sensors prepared in other embodiments of the present invention also have similar excellent performance to the sensors prepared in Example 2, with high sensitivity and specificity, and easy recovery.
[0067] Comparative Example 1
[0068] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0069] 100 mg EDC and 100 mg NHS were dispersed in 10 mL of PBS buffer, and 5 mL of 2.89 mol / L polyethylene glycol dicarboxylic acid was added. The mixture was stirred and activated at room temperature for 4 h. Then, 5 mL of PBS buffer solution containing 0.256 g / mL Fe3O4-NH2 particles (prepared above) was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated, washed three times with deionized water, and then dispersed again in 10 mL of PBS buffer. 200 mg EDC and 200 mg NHS were added and activated for 4 h. Then, 5 mL of 0.86 mol / L 1,6-hexanediamine PBS buffer was added, and the reaction was continued for 24 h. After the reaction, the particles were magnetically separated and washed three times with deionized water to obtain amidated Fe3O4-NH2 nanoparticles.
[0070] 0.83 g of the above amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.16 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. After the reaction was completed, Fe3O4-RhB was obtained by magnetic separation, washing three times with ethanol and three times with deionized water, and vacuum drying at 30 °C.
[0071] The product of Comparative Example 1 was subjected to Cr testing according to the performance study method of Test Example 3. 6+ Ion sensing experiments revealed no significant fluorescence change before and after sensing, indicating that the device lacks sensing and detection capabilities.
[0072] Comparative Example 2
[0073] 5.0 g of 1,6-hexanediamine was weighed and dissolved in 30 mL of ethylene glycol. The solution was stirred in a 50 °C water bath until completely dissolved. Then, 1.0 g of FeCl3·6H2O and 2.0 g of anhydrous sodium acetate were dissolved by sonication. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190 °C for 6 h. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35 °C to obtain Fe3O4-NH2 nanoparticles.
[0074] 0.83 g of the above-mentioned amidated Fe3O4-NH2 nanoparticles were weighed and dispersed in 180 mL of deionized water. 5 mL of 0.16 mol / L Rhodamine B aqueous solution was added, and the mixture was stirred thoroughly at room temperature for 100 min. Subsequently, 3.49 g of acrylamide, 11.02 g of sodium hexametaphosphate, and 9.96 g of potassium persulfate were added, and the mixture was ultrasonically stirred vigorously at 35 °C for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor (Fe3O4 / RhB@PAM) was obtained after magnetic separation, washing three times with ethanol and deionized water, and vacuum drying at 30 °C.
[0075] The sensor performance study revealed that, compared with the sensor Fe3O4 / RhB@PAM prepared in Example 2, the Fe3O4-NH2 nanoparticles of the sensor Fe3O4 / RhB@PAM obtained in Comparative Example 2 lacked the amidation process, resulting in a reduction in the amount of RhB embedded in the sensor prepared in Comparative Example 2. Under the same detection conditions, the sensor had poorer sensitivity, a higher detection limit, and a longer sensing time.
[0076] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.
Claims
1. A responsive magnetic Cr(VI) sensor, comprising a Fe3O4 / RhB@PAM nanosensor formed by embedding Fe3O4-NH2 nanoparticles with Rhodamine B through the self-polymerization of acrylamide, wherein the preparation method of the responsive magnetic Cr(VI) sensor includes the following steps: (1) Carbodiimide EDC and N-hydroxysuccinimide NHS were dispersed in phosphate buffer PBS, polyethylene glycol dicarboxylic acid was added, and the mixture was stirred and activated at room temperature for 4-6 h. Then, PBS buffer solution of Fe3O4-NH2 particles was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated, washed, and then dispersed again in PBS buffer. EDC and NHS were added and activated for 4-6 h. Then, 1,6-hexanediamine PBS buffer was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated and washed to obtain amidated Fe3O4-NH2 nanoparticles. (2) The amidated Fe3O4-NH2 nanoparticles obtained in step (1) were dispersed in deionized water, and Rhodamine B aqueous solution was added. The mixture was stirred thoroughly at room temperature for 100 min. Acrylamide, sodium hexametaphosphate and potassium persulfate were then added. The mixture was stirred violently with ultrasound at 35~75℃ for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor was obtained by magnetic separation, washing with ethanol and deionized water respectively, and vacuum drying.
2. The responsive magnetic Cr(VI) sensor according to claim 1, characterized in that, In the Fe3O4 / RhB@PAM nanosensor, the mass percentages of Fe3O4-NH2 nanoparticles, Rhodamine B, and polyacrylamide PAM are 8.7%~17.7%, 3.5%~17.8%, and 73.4%~86.3%, respectively.
3. A method for fabricating a responsive magnetic Cr(VI) sensor, comprising the following steps: (1) Carbodiimide EDC and N-hydroxysuccinimide NHS were dispersed in phosphate buffer PBS, polyethylene glycol dicarboxylic acid was added, and the mixture was stirred and activated at room temperature for 4-6 h. Then, PBS buffer solution of Fe3O4-NH2 particles was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated, washed, and then dispersed again in PBS buffer. EDC and NHS were added and activated for 4-6 h. Then, 1,6-hexanediamine PBS buffer was added, and the mixture was stirred and reacted for 24-30 h. After the reaction was completed, the mixture was magnetically separated and washed to obtain amidated Fe3O4-NH2 nanoparticles. (2) The amidated Fe3O4-NH2 nanoparticles obtained in step (1) were dispersed in deionized water, and Rhodamine B aqueous solution was added. The mixture was stirred thoroughly at room temperature for 100 min. Acrylamide, sodium hexametaphosphate and potassium persulfate were then added. The mixture was stirred violently with ultrasound at 35~75℃ for 1.0 h. The entire process was carried out under nitrogen protection. After the reaction was completed, the responsive magnetic Cr(VI) sensor was obtained by magnetic separation, washing with ethanol and deionized water respectively, and vacuum drying.
4. The preparation method according to claim 3, characterized in that, In step (1), the concentrations of carbodiimide EDC and N-hydroxysuccinimide NHS dispersed in phosphate buffer PBS were both 10 mg / mL.
5. The preparation method according to claim 3, characterized in that, In step (1), the weight ratio of carbodiimide EDC, N-hydroxysuccinimide NHS, polyethylene glycol dicarboxylic acid and Fe3O4-NH2 particles is 0.1:0.1:(1.55~2.35):(0.99~1.51).
6. The preparation method according to claim 3, characterized in that, In step (1), the weight ratio of 1,6-hexanediamine to Fe3O4-NH2 particles in the added 1,6-hexanediamine PBS buffer is 1:(1.98~3.02).
7. The preparation method according to claim 3, characterized in that, In step (2), the weight ratio of amidated Fe3O4-NH2 nanoparticles, Rhodamine B in Rhodamine B aqueous solution, acrylamide, sodium hexametaphosphate, and potassium persulfate is (0.21~0.83): (0.07~0.43): (1.77~3.49): (2.44~11.02): (1.37~9.96).
8. The preparation method according to claim 3, characterized in that, The Fe3O4-NH2 nanoparticles described in step (1) were prepared by a solvothermal method. 1,6-hexanediamine was weighed and dissolved in ethylene glycol at a weight-to-volume ratio of 1:
6. The solution was stirred in a 50°C water bath until completely dissolved. Then, FeCl3·6H2O and anhydrous sodium acetate were dissolved by ultrasonication. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 190°C for 6 hours. After cooling to room temperature, the solution was magnetically separated, washed three times with deionized water and ethanol, and dried under vacuum at 35°C to obtain Fe3O4-NH2 nanoparticles. The weight ratio of FeCl3·6H2O, anhydrous sodium acetate and 1,6-hexanediamine was 1:2:
5.
9. The responsive magnetic Cr(VI) sensor according to claim 1 in acidic Cr-containing environments 6+ Applications in wastewater testing.
10. The application according to claim 9, characterized in that, The amount of the sensor used is 0.05 mg / mL.
Citation Information
Patent Citations
Nano-crystal cellulose fluorescent probe for detecting metal ions and preparation method thereof
CN108559485A
A fluorescence sensor based on rhodamine 6G derivative and its fabrication method
CN112708015B
Water soluble biocompatible fluorescent magnetic nanoclusters and preparation method thereof
CN105936820A